Application of nondestructive evaluation (NDE) technologies throughout cold chain logistics of seafood: Classification, innovations and research trends. (15th March 2022) - Ye, Beibei; Chen, Jian; Fu, Linglin; Wang, Yanbo
Abstract: The global trade of seafood often involves many complex cold chain logistics. Therefore, it is necessary to seek reliable techniques applied to cold chain logistics for quality control and safety supervision. Traditional evaluation methods, such as sensory evaluation, chemical and physical measurements, have particular limitations such as poor accuracy, destructiveness, and cumbersome feature. Recently, an increasing number of nondestructive evaluation (NDE) technologies are explored and employed in cold chain logistics. NDE technologies can monitor the trackability of cold chain logistics operations in real-time and detect the quality and safety of seafood at critical points, aiming to enable a seamless connection throughout cold chain logistics. Herein, the applications of these NDE technologies throughout cold chain logistics of seafood were summarized based on (1) Classifying these NDE technologies depending on different evaluation needs during the cold chain logistics; (2) Comparing the advantages and limitations of these technologies for evaluating the quality of seafood; (3) Discussing the real applications and research trends of NDE technologies during cold chain logistics. Generally, this review can contribute to promoting the innovation of NDE technologies and guide the appropriate selection of NDE approaches for the seafood industry throughout cold chain logistics. Graphical abstract: Image 1 Highlights: Nondestructive monitoring and detection technologies are reviewed. Applications of nondestructive evaluation (NDE) technologies in seafood field are introduced. The advantages and limitations of NDE technologies are compared. The research trends of NDE technologies are discussed.